Kepastian Hukum Jaminan Hari Tua Bagi Pekerja Pasca Pemutusan Hubungan Kerja - Renpina Siringo; Yulia Rahmawati; Syaharani Zahra; Rifqi Ahmad Ilhamy (DPPM Universitas Pelita Bangsa, 2026)
The Old-Age Security (JHT) program is a form of employment-based social security designed to provide economic protection for workers, particularly when they enter a non-productive phase or upon the termination of their employment. However, in practice, the fulfillment of JHT rights for workers following termination of employment (PHK) continues to give rise to various legal issues, particularly regarding legal certainty in the benefit disbursement process. Research findings indicate that, while the regulatory framework for JHT provides a basis for legal protection for workers after termination, implementation issues persist—specifically concerning eligibility requirements, disbursement timelines, and workers' understanding of their rights. Consequently, there is a need to strengthen regulations, improve public awareness and outreach, and ensure consistent implementation by the social security administrator